Perceived Neighborhood Characteristics and Experiences of Intimate Partner Violence: A Multilevel Analysis - Thulin, Elyse J. (Journal of interpersonal violence, 2021)
Within a lifetime, one in four women and more than one in 10 men will experience intimate partner violence (IPV). Researchers have begun to examine physical and social neighborhood risk factors of IPV, often using cross-sectional data. Most studies focus on risk or promotive factors. Often, neighborhood factors are studied through the lens of social disorganization theory, which focuses on how a neighborhood slips into a violent and crime-ridden place. Busy streets theory provides an alternative perspective, focusing on how building up community assets and resources may help create a safe and vibrant neighborhood. A conceptual approach that utilizes risk and promotive neighborhood variables may help develop new conceptual frameworks for understanding how context may decrease risk for, or moderate, the negative consequences of IPV. Using five waves of data from a 24-year longitudinal study, we employ multilevel linear regression models to examine the trajectory of IPV experiences in relation to positive perceptions of neighborhood, neighborhood cohesion, and informal social control in individuals aged 28 to 33 years. We control for the neighborhood and individual-level risk factors of alcohol consumption, drug use, observed neighborhood violence, and demographic factors of age, race, sex, and socioeconomic status. We found that positive perceptions of neighborhood, alcohol consumption, drug use, economic need, and observed neighborhood violence are associated with IPV. Levels of IPV risk were relatively constant within individuals across waves, but varied significantly between individuals. The measure of positive perceptions of neighborhood is derived from busy streets theory, which may be a useful conceptual framework for understanding how neighborhoods may contribute to positive social contexts that can protect residents from IPV experiences, and potentially other violent behavior. Additional research examining promotive social neighborhood features derived from busy streets theory may help expand our understanding of contextual factors that affect IPV.